Knowledge and practices of water and sanitation and prevention of water-borne diseases among the residents of Wabgaon village - Mittal, Gaurav C.; Sundar, R. Naveen Shyam; A., Prashanth (International Journal Of Community Medicine And Public Health, 2023)
Background: Globally 1.339 billion U-5s and 79 thousand neonates aged 0-27 days were estimated to be dead due to diarrhoea. India, Nigeria, Afghanistan, Pakistan, and Ethiopia accounts for more than half of the deaths caused by diarrhoea. Our objectives are to understand the knowledge and practices of WASH, preventive and treatment measures of diarrheal diseases, the feeding practices and hygiene among the mothers in the rural village of Wardha district. Methods: This is a mixed method study with study participants including 72 families randomly selected along with the front-line workers. the descriptive analysis was carried out with the help of R software and other online statistical software. Results: 90.6 % had their source of water away from a contaminated place such as open drains, manure pits, solid waste disposal areas etc. Though 96.9% had toilets in their household only 93.8% actually used it. All of them washed their hands with soap after using the restroom. Mixed responses were obtained when people were asked about the line of action in case, they suffer from any of the acute diarrhoeal diseases. 90% of them prefer ORS during such times and the source of availing had mixed responses. Conclusions: An interventional study for the same can be carried out. Regular follow ups might assist in keeping the public free from such communicable discomforts.